CRIMINAL LAW ENFORCEMENT AGAINST ORANGUTAN TRAFFICKING AS PROTECTED ANIMALS - Mahendra Butar-Butar, Muhammad Yusril; Syahrin, Alvi; Marlina, Marlina; Trisna, Wessy (NOMOI Law Review, 2025)
Illegal trade in protected wildlife is an environmental crime and the Conservation of Living Natural Resources and Ecosystems as specified in Law Number 5 of 1990 concerning the Conservation of Living Natural Resources and Ecosystems, illegal trade in protected wildlife is still rampant and it is very damaging to the environmental ecosystem. So that this research is to elaborate on the legal protection of endangered animals in sustainable management of biological natural resources, law enforcement against the trade in protected animals according to the Law on Conservation of Biological Natural Resources and Ecosystems, and the judge's consideration of decision 1360/Pid.B/Lh/2022/Pn.Lbp and decision 95/Pid.B.Lh/2022/Pn.Bj on protected animal trafficking syndicates. The method used in this thesis is the normative juridical research method carried out by means of library materials or secondary materials. So that the author uses the statutory approach method (statude approach) and case approach (case approach). The data analysis method used is qualitative. The trade of Orangutans as protected wildlife is a criminal offense as specified in Article 21 paragraph (2) in conjunction with Article 40 paragraphs (2) and (4) of Law No. 5 of 1990. In Decisions 1360/Pid.B/LH/2022/PN.Lbp and 95/Pid.B/LH/2022/PN.Bnj , the panel of judges whose cases handed down sentences against the defendants, but the criminals generally given by the panel of judges were limited to the substance of the defendants in Law No. 5 of 1990, even though what the defendants had done had harmed the environment and endemic animals that were on the verge of extinction, so the author requests the Supreme Court of the Republic of Indonesia to request a special court for handling the environment and protected animals.